Principles of Lending Business Capital for Private Companies - Cut Ayu Erja Nabillah A. Beh; Rio Nugroho Fahmi; Rachmanda Yanuar Pradana; Carolina Septiani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The research, entitled "Principles of Lending Business Capital for Private Companies" aims to more deeply know and understand and analyze how the principles of lending business capital for private companies are based on the latest regulations. The research method used is normative research. Normative research is research using a statutory approach and draws on legal principles relating to legal entities, companies, individual companies. Based on the results of this study, it can be concluded that, First, an individual company is actually owned by the community in the form of a UD, but under the Job Creation Act, this company is a legal entity. However, in the realization of the establishment of this company, there are legal norms in lending to banks. Therefore, until now the problem of borrowing capital has not yet been resolved or directly reviewed so that the founder of the company can meet the requirements and conditions of the bank.